Crossed rows, row spacing, and seeding rates influence the growth and yield of two soybean cultivars - Balbinot Junior, Alvadi Antonio (2016)
This research aims to evaluate the growth of two soybean cultivars with determinate and indeterminate growth habits under different spatial plant arrangements, including crossed rows. Two experiments were conducted, one with BRS 294 RR cultivar, which has determinate growth habit and relative maturity of 6.3 and another with BRS 359 RR, which has indeterminate growth habit and relative maturity of 6.0. In both experiments, the randomized complete block design in a 2x2x2 factorial design with three replications was used. The treatments were formed by two row spacing (0.4 and 0.6 m), two seeding rates (375,000 and 562,500 seeds ha-1, with 81% germination) and two forms of sowing (crossed and uncrossed rows). The effect of plant arrangement on the soybean growth was different between cultivars. In general, for BRS 294 RR, vigorous vegetative growth and high branching, the growth of plant community was not affected by the spatial plant arrangement. However, the highest yield was observed in the 0.6 m row spacing. For BRS 359 RR, which has compact plant architecture, the highest plant density and the lowest row spacing promoted the growth and the soil cover by plant community, but did not affect the grain yield. In both cultivars, the soybean grain yield was not affected by crossed rows.